Product and Business Development of Another Path Game in Myhand Studio - Santosa, Daniel; Widyarto, Erdhi; Sanjaya, Ridwan (Journal of Business and Technology, 2023)
Game can be used for entertainment purpose and can also be used for educational purpose, in the world of game development there are many positions or roles in a team commonly referred to as a developer, the roles in a developer team are, programmer, artist, product manager, game marketing, market research etc, each position or role has its own responsibility for the success of a game that is in the development process, the market research position is one of the roles that is quite important for the success of a game product on the market, it does not mean other role do not play an important role in the success of a game product but the market research position is the main basis for making a game because this position will see directly to the market what trends are trending in the market or game genres that are in high demand by consumers, but after doing research on student related to game developing is very unfortunate very few students know about how to do market research and game product validation, here we will discuss how to do market research and product validation and a little bit about marketing game products in the market, in this journal will talk about how to make game step by step from doing market research, product validation and get to the point where developer get the data to make the game is demanded by the market, result of this research is before we need to make any decision about the game we need to make sure its not just assumption but the idea have a proof, to get the proof for ideas we can make a survei or posting things to social media and wait for responds, after some time waiting we found that our marketing strategy is working best with Facebook Ads, with small amount of money like $10 we got 9500 reach with only five days of campaign.